If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 1 = 7y + -1 Reorder the terms: 1 + 5y = 7y + -1 Reorder the terms: 1 + 5y = -1 + 7y Solving 1 + 5y = -1 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 1 + 5y + -7y = -1 + 7y + -7y Combine like terms: 5y + -7y = -2y 1 + -2y = -1 + 7y + -7y Combine like terms: 7y + -7y = 0 1 + -2y = -1 + 0 1 + -2y = -1 Add '-1' to each side of the equation. 1 + -1 + -2y = -1 + -1 Combine like terms: 1 + -1 = 0 0 + -2y = -1 + -1 -2y = -1 + -1 Combine like terms: -1 + -1 = -2 -2y = -2 Divide each side by '-2'. y = 1 Simplifying y = 1
| -7(7-5x)=27x | | 3(4x-6)=12x | | -90=5k-5(2+3k) | | 4+2x=5x-8 | | Logx+log(x-2)=0 | | 5.2a+11=68.2 | | 2m+4=8m-1 | | 4x-8=8+6 | | 5y+7=7y-1 | | 4x+3y+2z=15 | | 5x+4=6+5x | | x+3y+3z=16 | | 1+x+4=2+x+3 | | 4(6-3v)=96 | | 12m+5n-3m+10n= | | 160+.15m=241 | | 7x+117=-6x | | log[2]3x-6=4 | | -6x-3=3-6y | | 7x-35+3=6x-42 | | (x-6)-7=-3 | | 12p+19q+p-6q-3p= | | 1+x+2=3+x+4 | | 4(x+2)=30+3x | | X^2lnx-4lnx=0 | | 6a=80-4d | | 8x+10=8x-9 | | X^2=220+5 | | x^2+5x-3=3x+5 | | x^2+16x-15=0 | | 17=(-13)-(8x) | | 21-15=3(x-7) |